(untitled) (Praxis Educativa, 2023)
In the province of Santa Fe (Argentina) there are about 800 teachers working in schools with Intercultural Bilingual Education (EIB) modality, however, despite the more than thirty years of trajectory of EIB in the jurisdiction, the initial and/or continuous official training offer does not reach all the actors working in the modality and, in most of the registered cases, it does not go beyond the socialization of experiences; this situation has an impact on the strengthening of EIB in the territory. The aim of this work is to reconstruct the challenges of public teacher training policies in Santa Fe if the objective is to strengthen EIBproposals; for this purpose, the relationship between the official training offer for non-qualified teachers and the functions demanded of them by the institutional EIB project is made explicit.